2018
DOI: 10.1038/s41598-018-32993-z
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression and oxytocin as possible markers of positive emotions in horses

Abstract: Behavioural and physiological markers of discrete positive emotions remain little investigated in animals. To characterise new markers in horses, we used tactile stimulations to induce emotional situation of contrasting valence. In the Gentle grooming group (G, N = 13) horses were gently groomed during 11 sessions on the body areas they appreciated the most. Horses in the Standard grooming group (S, N = 14) were groomed using a fixed procedure, reported to induce avoidance reactions in some horses. At session … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 69 publications
2
65
0
1
Order By: Relevance
“…Another study, conducted on only three horses showed that they recalled correctly complex problem-solving strategies seven years later 23 . Regarding the more specific human-animal relationship, horses could remember interactions they had had with human beings five months 26 , or even a year previously 25 . The present study shows that beyond remembering what they have learned or the interactions they have had with humans, horses also have an excellent memory of people and particularly of their faces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, conducted on only three horses showed that they recalled correctly complex problem-solving strategies seven years later 23 . Regarding the more specific human-animal relationship, horses could remember interactions they had had with human beings five months 26 , or even a year previously 25 . The present study shows that beyond remembering what they have learned or the interactions they have had with humans, horses also have an excellent memory of people and particularly of their faces.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it can correctly recall the conditioning procedure several years later 23,24 . In addition, horses can also remember the type of relationship (positive or negative) they had experienced with a human several months after the interaction 25,26 . However, no information is available about a horse's potential capacity to remember faces over time.…”
mentioning
confidence: 99%
“…Therefore, reacting in a flexible way to the animal's behavioural indications of preference, and consequently stroking different body areas, would mimic the social behaviour of cattle more closely and might lead to more positive reactions. While studies in horses have shown that grooming styles reacting to the animals' signals lead to more positive reactions [23], there is no study investigating reactive stroking treatments in cattle yet.…”
Section: Introductionmentioning
confidence: 99%
“…As this experiment did not include a treatment where the animals were stroked without any auditory stimulation, we cannot infer any information on whether gentle talking in general enhances or diminishes the positive effects of stroking, but the results are very similar to our previous study, where the animals were stroked without acoustic stimulation. Stroking can elicit quite strong effects on physiology and behavior in different species (rats: Holst et al, 2005 ; cows: Schmied et al, 2010 ; cats: Gourkow et al, 2014 ; lambs: Coulon et al, 2015 ; horses: Lansade et al, 2018 ), which might exceed possible consequences of small differences in auditory stimuli. Regarding the absence of significant differences in behavior, it seems plausible that the heifers did not discern the two auditory stimuli, at least not to an extent where it would have affected their behavior.…”
Section: Discussionmentioning
confidence: 99%